The Conceptualization of Religious Moderation in Islamic Economic Jurisprudence: A Study of Al-Risalah by Imam Al-Shafi’i - Tanzilulloh, M Ilham; Saleh, Abdul Mun'im (Invest Journal of Sharia & Economic Law, 2022)
The concept of religious moderation has gained significant relevance in Islamic legal thought, particularly in addressing the contemporary challenges in Islamic economic law and governance. The rapid expansion of Islam to diverse regions and interactions with various cultural influences have shaped the evolving interpretations of revelation texts, including their application to economic activities. Imam al-Shafi'i, through Al-Risalah, developed foundational theories of fiqh (Islamic jurisprudence) that emphasized balancing adherence to sacred texts with rational flexibility to address new and complex cases, particularly in areas such as contracts, trade, and financial ethics. His methodology sought to reconcile the two intellectual tendencies of his time—ahl al-hadith (textualists) and ahl al-ra'y (rationalists)—by rejecting arbitrary reasoning (istihsan) and promoting analogical reasoning (qiyas) under the framework of divine law. This study explores how religious moderation, as conceptualized by al-Shafi'i, influenced the development of al-qawa'id al-fiqhiyyah (legal maxims), which remains central to resolving contemporary legal-economic issues. Through a philosophical qualitative approach, this research examines how al-Shafi'i’s legal thought provides a sustainable framework for balancing textual authority and adaptability in Islamic economic jurisprudence, ensuring that legal rulings are both divinely grounded and responsive to socioeconomic contexts.